Survival benefit of primary and metastatic tumor resection for colon cancer with liver metastases: A population based, propensity score-matched study - Qiao, Yunfeng; Qiao, Yunfeng; Li, Huijun; Fu, Jinge; You, Shuping (Frontiers in Surgery, 2022)
Background: Colon cancer remains one of the most common malignancies and we aimed to evaluate whether surgery has an effect on the survival of metastatic colon patients. Methods: We analyzed 7,583 metastatic colon patients from the Surveillance, Epidemiology, and End Results (SEER) registry between January 2010 and December 2015. Using Cox proportional hazards models and Kaplan-Meier curves, the overall survival rate (OS) and cancer-specific survival rate (CSS) months (m) were evaluated with corresponding 95% confidence intervals (95% CIs). Propensity score matching (PSM) was performed to adjust for potential baseline confounding of all comparison groups. Results: In general, receiving both primary and metastatic tumor resection (PMTR) remarkably improved OS and CSS compared with only primary tumor resection (PTR) after PS matching (PSM) (P<0.05), with a significantly improved OS (HR=0.74, 95%CI=0.69-0.80) and CSS (HR=0.71, 95%CI=0.66-0.76) in all stage M1 colon patients. The stratification analysis indicated a significant difference between OS and CSS in M1a and M1b stages. After PSM, PMTR was found to be associated with remarkably improved OS and CSS for patients with liver metastases but not associated with OS and CSS of patients with lung metastases in both M1a and M1b stage. Conclusions: The results from this large SEER cohort supported PMTR might improve the survival of colon patients with liver metastases on the basis of chemotherapy.